Combined Cognitive-Psychological-Physical Intervention Induces Reorganization of Intrinsic Functional Brain Architecture in Older Adults. (24th February 2015) - Zheng, Zhiwei; Zhu, Xinyi; Yin, Shufei; Wang, Baoxi; Niu, Yanan; Huang, Xin; Li, Rui; Li, Juan
Abstract : Mounting evidence suggests that enriched mental, physical, and socially stimulating activities are beneficial for counteracting age-related decreases in brain function and cognition in older adults. Here, we used functional magnetic resonance imaging (fMRI) to demonstrate the functional plasticity of brain activity in response to a combined cognitive-psychological-physical intervention and investigated the contribution of the intervention-related brain changes to individual performance in healthy older adults. The intervention was composed of a 6-week program of combined activities including cognitive training, Tai Chi exercise, and group counseling. The results showed improved cognitive performance and reorganized regional homogeneity of spontaneous fluctuations in the blood oxygen level-dependent (BOLD) signals in the superior and middle temporal gyri, and the posterior lobe of the cerebellum, in the participants who attended the intervention. Intriguingly, the intervention-induced changes in the coherence of local spontaneous activity correlated with the improvements in individual cognitive performance. Taken together with our previous findings of enhanced resting-state functional connectivity between the medial prefrontal cortex and medial temporal lobe regions following a combined intervention program in older adults, we conclude that the functional plasticity of the aging brain is a rather complex process, and an effective cognitive-psychological-physical intervention is helpful for maintaining a healthy brain and comprehensive cognition during old age.